The moderating effects of individual differences in baseline episodic memory on acute exercise benefits in memory. - Patrick, Zakary; Mann, Reese; Hillman, Charles H.; Jung, Myungjin; Hayes, Scott M.; Miller, Stephanie E.; Undorf, Monika; Heffernan, Kevin; Loprinzi, Paul (Memory & Cognition, 2026)
Acute vigorous-intensity exercise has been shown to positively impact cognitive function, including long-term episodic memory performance. However, few studies have investigated whether individual differences in baseline memory influence the relationship between acute exercise and memory performance. Thus, the purpose of this experiment was to evaluate baseline episodic memory as a potential moderator of the relationship between acute exercise and memory. 213 young adults completed a within-subjects, counterbalanced design. Participants completed two conditions: a 20-min vigorous-intensity exercise condition and a non-exercise control condition. For each condition, two list-learning memory assessments were employed, one conducted after a 20-min delay and another after a 24-h delay. Baseline long-term episodic memory was evaluated from the control condition using participants' episodic memory performance at the 24-h delay. We found that baseline episodic memory moderated the relationship between acute exercise and memory performance: participants with lower baseline episodic memory ability showed the greatest increases in long-term episodic memory performance following a 20-min vigorous-intensity exercise. These results suggest that individual differences in memory performance should be considered as an important moderator when evaluating the relationship between acute exercise and long-term episodic memory function.